Biofluid mechanics - Mazumdar, Jagannath (Singapore World Scientific Publishing Company, 2016)
This book provides an in-depth study of biological fluid dynamics through the lens of fluid mechanics, focusing on its applications to complex biological systems. It integrates engineering and life sciences to address biomedical challenges, particularly in cardiovascular treatment. Designed for professionals and students, it highlights key applications of biofluid mechanics in modern biomedical engineering.
Includes bibliographical references and index
Keywords: Y đa khoa